Coriander Oil Reverses Dexamethasone-Induced Insulin Resistance in Rats - Mona F. Mahmoud; Noura Ali; Islam Mostafa; Rehab A. Hasan; Mansour Sobeh (Antioxidants)
In the present study, we aimed to investigate the effect of coriander oil on dexamethasone-induced insulin resistance in rats and characterize its chemical composition using gas chromatography-mass spectrometry (GC-MS). Rats were divided into five groups (n = 6): Normal control, insulin resistance (IR) control, IR + metformin (50 mg/kg/day, PO, Per Oral), IR + coriander oil low dose (0.5 mL/kg, PO), and IR + coriander oil high dose (1 mL/kg, PO). IR groups were injected with a dose of 10 mg/kg dexamethasone subcutaneously for four consecutive days. All groups received either vehicle or drugs daily for four days. Animal weights and pancreatic weights were measured, and oral glucose tolerance test was performed at the end of study. Fasting glucose, triglycerides (TG), total cholesterol (TC), HDL and insulin levels in serum, MDA, and GSH levels in pancreatic tissue were measured and HOMA-IR was calculated. Immunoexpression of apoptosis markers BAX, and BCL2 was measured in pancreatic tissues and BAX/BCL2 ratio was calculated. Histopathological examination of pancreatic tissues was also performed. Pancreatic weight, serum HDL, pancreatic GSH, and BCL2 were decreased while serum glucose, insulin, TG, TC levels, AUC of OGGT, HOMA-IR, pancreatic MDA, BAX, and BAX/BCL2 ratio were increased in IR rats. Histopathological examination showed congestion, vacuolation and hemorrhage in pancreatic islets. These changes were reversed by metformin and the high dose of coriander oil treatments. The obtained activities could be attributed to the presence of 21 volatile compounds, identified by GC-MS. Our study indicates that coriander oil can be used as an adjuvant antihyperglycemic agent in type 2 diabetes. Further experiments are needed to determine the therapeutic dose and the treatment time.